BUSINESS STRATEGIES TO INCREASE REVENUE ON CV. AYAM JANGKUNG - Aditiya; Vonny Tiara (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
With this research, it aims to be able to find out and analyze product strategies in an effort to increase revenue. The formulation of the problem in this study is how to analyze the strategy of the product in an effort to increase revenue. The purpose of this study is to find out and analyze product strategies in an effort to increase revenue. The type of research used is qualitative. The data collection technique used was by observation and interviewing 4 resource persons, namely: Owner, shop head, admin, and courier, The results of research in Ayam Jangkung are using product mix strategies, trademark use strategies, sales force strategies (sales) and mass media selection strategies. For this reason, the author draws conclusions and tries to give suggestions or input that might be useful as consideration for business owners, namely trying to expand the place, implement pricing strategies, develop new products and improve product quality, collaborate with influencers or celebrities to increase promotions to consumers and participate in bazaar events in order to introduce products to consumers.